Scanning electron microscopic evaluation of the effect of different root-end resection methods in the crack formation in root canals filled with mineral trioxide aggregate or calcium-enriched mixture cement - Eshaghali Saberi; Shima Bijari; Rahim Dinarvand (Wolters Kluwer Medknow Publications, 2022)
Background: There is some concern that root resection may alter the surface features and crack formation of the previously set orthograde material. The aim of this in vitro study was to evaluate the crack formation in orthograde mineral trioxide aggregate (MTA) and calcium-enriched mixture (CEM) plugs after root resection. Materials and Methods: This in vitro study was conducted on 170 extracted human maxillary anterior teeth. The teeth were randomly divided three experimental (n = 50) and control (n = 20) groups. In Group 1, after root canal treatment, half of the roots were cut with a bur, and the other half with an ultrasonic cutter. In Groups 2 and 3, after the 4-mm CEM and MTA plugs were placed and set, the root ends of half of the samples were cut with a bur and the other half by an ultrasonic cutter. The prevalence of cracks in the dentin and orthograde apical plugs of MTA and CEM was then assessed by scanning electron microscopy. Data were analyzed using the McNemar's, Chi-square, and Fisher's exact tests at P ≤ 0.05 level of significance. Results: In general, the prevalence of crack in dentin in Groups 2 and 3 was significantly higher than in the plug (P < 0.05). There was no significant difference in the prevalence of dentin crack in the studied groups (P > 0.05). The prevalence of crack in dentin was lower when the bur was used to cut off the end of the root, although the difference was not significant. The prevalence of crack in the plug was similar in CEM and MTA. Conclusion: Based on the results of this study, the prevalence of crack in dentin is always significantly higher than its prevalence in the plug, and the prevalence of crack in the plug was similar in CEM and MTA; then, when there is an orthograde access to the root canal and surgery is likely in future, MTA and CEM can be placed in an orthograde technique and it just resects the root during surgery.